Tindakan Aborsi Akibat Pemerkosaan Ditinjau Menurut Pandangan Islam, Bioetika Kedokteran dan Hukum Di Indonesia - Arsyzilma Hakiim; Mariyam Abdullah; Romelah Romelah (Syntax Corporation Indonesia, 2022)
Cases of violence against women in Indonesia continue to be in the spotlight, where there is an increase in cases from the previous year (Year 2020). In 2021, cases of violence against women emerged, namely cases of rape committed on 13 female students. Abortion is often an option as a way of suppressing the psychological trauma experienced by rape victims. The purpose of this study is to provide a review of the act of abortion due to rape in terms of Islamic views and medical bioethics as well as to provide an overview of the legal policy of abortion due to rape in a country that already has a legal abortion system due to rape, as well as to provide an overview of the impact of the policies that have been carried out. The type of research used is juridical empirical by collecting and analyzing, and focusing on Islamic views, bioethical rules, and applicable legal norms. The results of this study indicate that from a study of the Islamic religion, abortion due to rape is permitted before 40 days of gestation and is approved by the authorized team. Meanwhile, from the study of medical bioethics, it can be seen from medical indications in this case pregnancy due to rape which can cause mental health disorders by applying the principles of beneficence and non-maleficence, respect for human dignity and human right, respect for autonomy, and respect for confidentiality and privacy. . The act of abortion due to rape legally in Indonesia and several countries has been widely regulated, but in its implementation it is still a challenge in providing access to information and providing adequate health services.